Detangling spaghetti: Tracking deep ocean currents in the Gulf of Mexico. (2nd October 2017) - Curran, Mary Carla; Bower, Amy S.; Furey, Heather H.
ABSTRACT: Creation of physical models can help students learn science by enabling them to be more involved in the scientific process of discovery and to use multiple senses during investigations. This activity achieves these goals by having students model ocean currents in the Gulf of Mexico. In general, oceans play a key role in influencing weather patterns and climate. Water movement also affects fisheries through transport of various fish and invertebrate species as well as their predators and prey. Currents also impact the dispersion of pollutants, as in after an oil spill such as the catastrophe of the Deepwater Horizon oil rig in 2010. Currents exist deep in the ocean, and they do not always travel in the same direction as currents at the surface. This concept of the existence of ocean currents below the surface can be hard to explain, but we provide methodology for sharing this information in a way that is accessible to K–12 students, including the visually impaired. In addition to the NGSS standards and Ocean Literacy principles addressed, this activity has larger implications related to socioeconomics and international law.